PENGARUH KERJASAMA GURU DAN ORANG TUA TERHADAP PEMBENTUKAN KARAKTER KEDISIPLINAN PESERTA DIDIK DI SDN 3 CEMPAKA - HARTATI HARTATI (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to determine the effect of the collaboration between teachers and parents on the formation of disciplinary character of students using quantitative descriptive methods, the tools used in extracting the main data were questionnaires. From the results of statistical analysis pay attention to the significant level (ɑ) 5% and df (degrees of freedom) = the amount of data - 2 or 30-2 = 28, so that the t table is 1.701 at the 5% significant level. Thus, tcount = 80.9> ttable = 1.701, meaning that Ha which says "there is an effect of the cooperation between teachers and parents on the formation of disciplinary character of students in SD Negeri 3 Cempaka is accepted. The coefficient of reflection (R2) is 0.0694. This figure shows that the cooperation of teachers and parents on the formation of disciplinary character of students affects the disciplinary character of students by 6.94% and the remaining 93.06% is influenced by other factors. Thus teachers and parents are expected to always increase cooperation to develop and improve the quality of schools.